Enhancing security and incident response of Google Workspace for Education: A basis for developing an automated toolkit for privacy management - Canalita, Raymond D. (Animo Repository, 2023)
There is an increase in the usage of cloud solutions like Google Workspace among educational institutions, and these solutions offer several benefits, like flexibility, collaboration, and cost-efficiency. However, as cloud solutions usage has increased, threats like data breaches and malicious actor attacks are also growing. A toolkit developed originally for Google Workspace Business that uses Google Application Program Interface (Google API) was applied to an instance of Google Workspace Education to enhance the default capabilities of the platform on incident response. The value of the toolkit in managing security and incident detection is notable, especially in giving more context to incident response in analyzing audit data. Institutions with limited resources can benefit from the study on enhancing Google Workspace Education by automating security reporting using APIs. The developed toolkit would help institutions develop their information security requirements and better manage the security gap. Furthermore, this project includes proposal for breach management to the educational institution where the toolkit was tested to highlight the role of toolkit in incident response.